Assessment of effect of menopause on oral health and its awareness in population visiting dental OPD: a hospital-based study - Chand, Pooran; Dutt, Pranjali; Jurel, Sunit Kumar; Dasgupta, Santanu; Gautham, Harshika; Shetye, Akanksha Gopal (International Journal Of Community Medicine And Public Health, 2023)
Background: Menopause is a normal mechanism which takes part in every woman’s life. However, the awareness regarding menopause has to be highlighted effectively. Aim of this study was to assess the incidence and frequency of oral symptoms in postmenopausal women as well as to assess the level of awareness of menopause in women. Methods: A hospital-based study using a 60-item questionnaire was conducted on postmenopausal women with age range of 35-70 years for a period of three months. Statistical analyses were performed. Results on continuous measurements were presented on Mean±SD. Descriptive statistics with frequency and percentage were computed. Results: A total of 650 responses were received. In the present study, the mean age of menopause was 54 years. The most prevalent general symptoms reported were tiredness (89.8%), joint pains (89.7%) and irritability (76.5%). The most common oral manifestations of menopause were dryness of mouth (57.1%), altered taste (26.3%) and cracked corners of mouth (25.8%). About 39.8% of postmenopausal women had poor KAP score followed by 34.6% who had an average score while 18.3% had a good score and only 7.2% had scored excellent. Conclusions: Our study showed that the occurrence of classical menopausal symptoms of sweating and hot flushes was lesser in comparison to previous studies on Asian women. The increased incidence of dry mouth could lead to a rise in oral diseases. Moreover, a majority of postmenopausal women had a poor KAP score which showed that the awareness towards menopause needs to be increased.